METHOD AND DEVICE FOR HYDROTHERMAL CARBONIZATION (HTC) OF BIOMASS USING AN HTC SYSTEM - WITTMANN, TOBIAS; VON MASSOW, HANS-JOACHIM (2008)
Die Erfindung betrifft ein Verfahren der Prozessführung einer Anlage zur hydrothermalen Karbonisierung von Biomasse inkl. Trennung und Nutzung der Produkte sowie eine entsprechende Vorrichtung. The invention relates to a method of process control of a system for the hydrothermal carbonization of biomass, including separation and usage of products, and to a corresponding device. La présente invention concerne un procédé de conduite de processus dans une installation de carbonisation hydrothermale de biomasse, comprenant la séparation et l'utilisation des produits, ainsi qu'un dispositif correspondant.